Helmintofauna associada a leptodactylus fuscus (Anura: Leptodactylidae) em regiões de Cerrado, Pantanal e Caatinga no Brasil - Lins, Aline Gouveia de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Species differ in their environmental preferences, leading to processes in the community based in gradient variations that decrease as the distance increases. This process diminishes faster in heterogeneous landscapes, especially in solid areas of bands like South American open diagonally, that is characterized by horizontal stratification environments, presenting a landscape mosaic that extends from the Caatinga to the regions of Chaco, through the Pantanal. The Cerrado, Pantanal and Caatinga are characterized by great diversity of vertebrate anuran species, including the host Leptodactylus fuscus. These regions are inserted in the open diagonal South American. The composition and the relationship between parasite-host infra-populations of helminth species associated with L. fuscus specimens were described in three different regions of Brazil. Amphibians are found in a variety of habitats and exhibit different reproductive and behavioral patterns, considered good models to study parasitology. The study evaluated if there is a decay on the similarity between geographically distant communities and concluded that these two variables are positively associated. This study assessed 155 hosts and found a total of 16 taxa: Aplectana membranosa, Aplectana pintoi, Schankiana formosula, Cosmocerca podicipinus, Oswaldocruzia lopesi, Oxyascaris necopinus, Glypthelmins linguatula, Catadiscus cf. marinholutzi, Physaloptera sp., Physalopteroides sp., Rhabdias sp., metacercariae (Diplostomidae), nematodes of Cosmocercidae, larval cestode, cystacant and encysted unidentified larvae. The helminth component community of the Pantanal and Cerrado were the most similar and showed higher species sharing (n = 10) generating another clade in the cluster for Caatinga area. Some helminth species contributed to this dissimilarity influencing the results of the canonical discriminant analysis, characterizing the grouping formed for each biome. The taxonomic variation among hosts of different localities may be a result of the diversification of the host species during the evolutionary period, considered a complex species or even by the environmental characteristics of each site. This study presents a characterization of helminth fauna associated with L. fuscus and contributes to ecological studies of the host-parasite relationship.

As espécies diferem em suas preferências ambientais, isto conduz a processos na comunidade baseados em variações de gradiente que decrescem com o aumento da distância, sobretudo em faixas de áreas contínuas como a diagonal aberta sul-americana, apresentando um mosaico paisagístico que se estende desde a Caatinga até as regiões do Chaco. O Cerrado, Pantanal e Caatinga são caracterizados pela grande diversidade de espécies de vertebrados anuros, incluindo o hospedeiro Leptodactylus fuscus, e estas regiões estão inseridas na diagonal aberta Sul Americana. Foi descrita a composição e a relação entre parasita-hospedeiro de infra-populações das espécies de helmintos associados com espécimes do Leptodactylus fuscus em três regiões diferentes do Brasil. Os anfíbios são encontrados em uma variedade de habitats e exibem diversos padrões reprodutivos e comportamentais, por isso são considerados bons modelos de estudo para a parasitologia. O trabalho avaliou se ha um decaimento na similaridade entre comunidades geograficamente distantes, e concluiu que estas duas variáveis se associam positivamente. Foram avaliados 155 espécimes de hospedeiros totalizando 16 taxas de helmintos, Aplectana membranosa, Aplectana pintoi, Schankiana formosula, Cosmocerca podicipinus, Oswaldocruzia lopesi, Oxyascaris necopinus, Glypthelmins linguatula, Catadiscus cf. marinholutzi, Physaloptera sp., Physalopteroides sp., Rhabdias sp., metacercárias da Família Diplostomidae, nematodas da Família Cosmocercidae, larvas de cestóide, cistacanto e larvas encistadas não identificadas. A comunidade componente de helmintos do Pantanal e Cerrado foram as mais similares e tiveram um maior compartilhamento de espécies (n=10) gerando um ramo a parte no cluster para a região da Caatinga. Algumas espécies de helmintos contribuíram para essa dissimilaridade influenciando os resultados da análise discriminante canônica, caracterizando os agrupamento formados para cada bioma. As variações taxonômicas entre os hospedeiros das diferentes localidades pode ter sido resultado da diversificação da espécie hospedeira durante o período evolutivo que é considerada um complexo de espécies ou ainda pelas características ambientais de cada local. Apresentamos uma composição da helmintofauna associada a L. fuscus além de contribuir para estudos ecológicos sobre a relação parasita-hospedeiro.
Helminthfauna associated with leptodactylus fuscus (Anura: Leptodactylidae) in areas of Cerrado, Wetland and Caatinga of Brazil
Keywords: Leptodactylus fuscus; Anuros; Diagonal aberta; Helmintofauna; Dissimilaridade; Anurans; Open diagonal; Helminthfauna; Distance decay; Parasite diversity